2004
DOI: 10.1345/aph.1d564
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Sufentanil Citrate with Levobupivacaine HCl in NaCl 0.9% Infusion After Microwave Freeze–Thaw Treatment

Abstract: Within the limits defined here, a mixture of sufentanil citrate and levobupivacaine HCl may be prepared in advance and kept frozen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…A stability study of sufentanil citrate (1 µg/mL) and levobupivacaine HCl (1.25 µg/mL) in saline showed that the admixture was stable for at least 70 days at 4°C and after one freeze–thaw cycle [21]. During this time, sufentanil concentrations remained greater than 90% of the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…A stability study of sufentanil citrate (1 µg/mL) and levobupivacaine HCl (1.25 µg/mL) in saline showed that the admixture was stable for at least 70 days at 4°C and after one freeze–thaw cycle [21]. During this time, sufentanil concentrations remained greater than 90% of the initial concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Although the current practice for preparing dulanermin IV administration does not involve freezing and thawing, utilization of a centralized intravenous additive service (CIVAS) where the IV solution for small molecule drugs is stored frozen is quite common and gaining popularity [35][36][37]. Essentially, CIVAS would prepare the IV solutions in advance, store the solution in a freezer, and thaw the frozen solutions prior to administration.…”
Section: Discussionmentioning
confidence: 99%
“…The stability for a period of 24 hours at least was described for 17 drugs in 8 papers [22,[26][27][28][29]34,41,43,48]. Indeed, only 3 teams have tested the long-term stability after MFTT, the first for ganciclovir after 7 days [51], the second for ceftizoxime after 30 days [36] and the third for 19 drugs after 11 to 70 days described in 18 papers [16,23,31,38,39,46,49,50,[52][53][54]58,60,62,[64][65][66]73].…”
Section: Discussionmentioning
confidence: 99%